PERANCANGAN FASILITAS KERJA PROSES PEMBUATAN BAKSO PADA USAHA KECIL MENENGAH MORO ASIH - Al Ayubi, Moh Galih; Sri Zetli (LPPM Universitas Putera Batam, 2024)
This study was conducted on employees at UKM Moro Asih, where the process of making meatballs is still carried out without a work table, which can lead to Musculoskeletal Disorders (MSDs) in employees. Through the distribution of the Nordic Body Map (NBM) questionnaire, it was found that 2 out of 3 workers had a